Reducing Fear and Enhancing Aesthetics: Orthodontic Management with Video Self-Modeling in an Adolescent with Autism Spectrum Disorder - Dutta, Kripa; Saha, Swagata; Reddy, Harshita; Reenayai, Ngangbam; Shetty, Rajmohan Y.; Rai, Kavita; Raman Nair, Manju (Journal of Health and Allied Sciences NU, 2024)
Introduction Autism spectrum disorder (ASD) presents challenges in social interaction and communication, particularly in the context of orthodontic treatment where patients may experience heightened anxiety. This case report introduces an innovative approach that utilizes video self-modeling (VSM) to address these challenges and enhance the orthodontic treatment experience for adolescents with ASD.Case Report An 11-year-old female patient with ASD required orthodontic treatment. Conventional behavioral guidance techniques were unsuccessful because of the patient's anxiety and sensory sensitivity. Utilizing VSM, we crafted personalized video content to illustrate the dental procedure, significantly alleviating patient's fear and anxiety. This approach led to the successful completion of her orthodontic treatment.Conclusion This case report underscores the effectiveness of VSM as a valuable behavioral guidance technique in orthodontic treatment for adolescents with ASD. By alleviating anxiety and fear, VSM has the potential to significantly enhance the dental care experience and promote improved oral health and well-being in this specific patient population.
Keywords: autism spectrum disorder; orthodontic treatment; behavior guidance techniques; video self-modeling (VSM); anxiety; sensory sensitivities; oral health; dental care; adolescent